A Critical Review of Strategic Directions for Enhanced Employment Creation in Zambia - Mwange, Austin (IJRDO - Journal of Applied Management Science, 2018)
This is a critical review of the various strategic directions, measures and programmes that the Zambian Government has formulated and attempted to implement in an effort to create valuable, inclusive and sustainable job opportunities. The paper reviews the 2015 Youth Policy, the Vision 2030, the 7NDP. The paper recommends that government should religiously implement all the programmes under various strategic options aimed at achieving enhanced employment creation in the Zambian economy within the set parameters of the Medium-Term Expenditure Framework (MTEF) 2018 - 2021. In so doing, the objectives of the MTEF shall be achieved as well as employment creation.